Kecerdasan Emosional Tokoh Totto Chan dalam Novel Madogiwa no Totto Chan Karya Tetsuko Kuroyanagi Menurut Teori Goleman Sebuah Analisis Psikologi - Noor Laili Faizah; Sri Oemiati (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2020)
This research is a descriptive psychological analysis study according to Goleman's theory of the emotional intelligence of Totto Chan in the novel Madogiwa no Totto chan by Tetsuko Kuroyanagi. The purpose of this study was to determine the level of emotional intelligence of Totto Chan in the novel Madogiwa No Totto Chan by Tetsuko Kuroyanagi. The results of the analysis in this study indicate that the character of Totto Chan has seven elements of emotional intelligence. This is indicated by the confidence to succeed very high, always trying to find out and try new things, the main character plans well and does not despair to achieve goals when intending to do something, the main character has self-control in adjusting his desires to the demands of the environment, the main character has a very high relationship with other people where the main character is able to understand their situations and conditions, the main character communicates well, the main character can be cooperative with others. Therefore Totto Chan's emotional intelligence is high.Â